Pattern of Skull and Facial Bone Fracture in Craniomaxillofacial Trauma Associated with Traumatic Brain Injury: A Retrospective Analysis at Tertiary Hospital - Prasetyo, Eko; Oley, Maximillian C.; Tjungkagi, Ferdinan; Manuhutu, Yovanka N.; Sonbay, Antonius E. (e-CliniC, 2024)
Abstract: Trauma is one of the primary causes of death during the first four decade.  Craniomaxillo-facial (CMF) trauma has become a common presentation in emergency departments of hospitals. The most presentation of CMF trauma includes skull and facial bone fracture and traumatic brain injury (TBI). This study aimed to obtain the pattern of skull and facial bone fracture in craniomaxillofacial trauma associated with traumatic brain injury. This was a retrospective study conducted on 501 patients from January 2020 to December 2021. Demographic data included age, sex, length of stay (LOS), and Glasgow coma scale (GCS). The results showed that from the total 501 patients with skull and facial bone fracture with or without traumatic brain injury, 406 (81%) were males and 95 (19%) were females. The age range of the patients was between 2 years and 86 years (mean±SD 33.9±18.2). The most common patient affected age ranged from 21 to 30 years. The average of LOS was 7.2±5.7 days (0-33) and the mean of GCS was 10.2±4.2. Based on types of cases, there were 232 cases (60%) of skull and facial bone fractures accompanied by TBI; 154 cases (40%) of only skull and facial bone fracture; and 339 (59.5%) cases of only TBI. In conclusion, the distribution of TBI increases in those with skull and facial bone fractures. On the other hand, the distribution of TBI is more common without fracture. Hence every skull and facial bone fracture must be carefully evaluated clinically and radiologically to rule out any underlying TBI. Keywords: skull and facial bone fracture; craniomaxillofacial trauma; traumatic brain injury